Lanthanide Chlorides Decrease the Antioxidant Property of Human Serum Albumin - Mahmood Payeghadr; Gholamreza Rezaei Behbehani; Monir Shalbafan (Orbital: The Electronic Journal of Chemistry, 2017)
Substantial conformational changes of human serum albumin, HSA, induced by Lanthanide chlorides (Ce3+, La3+, Er3+) in phosphate buffer, 10 mmol L-1 at pH 7.4, was studied by Isothermal Titration Calorimetry, ITC. The strong negative cooperativity of Lanthanide chlorides interaction with HSA recovered from the extended solvation model, indicates that HSA denatures as a result of its interaction with toxic Lanthanide chlorides.DOI: http://dx.doi.org/10.17807/orbital.v9i1.941